Disobedient citizenships. Paradoxes and tensions around rights and what counts as human in disputes over abortion legalization - San Pedro, Constanza (Área Feminismos, Género y Sexualidades del Centro de Investigaciones "María Saleme de Burnichón" de la Facultad de Filosofía y Humanidades, Universidad Nacional de Córdoba, 2021)
In the following pages I am interested in problematizing the notion of citizenship from a critical perspective that allows us to put into dialogue the idea of recognition and rights, in a specific normative framework that includes sexual norms, legislation, and a web of meanings and moral practices that operate as a grid of intelligibility of bodies and of what is considered human. Following Butler (2010, 2012), this normative framework distributes recognition in a differential way between those who adapt or do not adapt to the norm, between those who are legible and those who are not. Thus, some will be deserving of certain rights and others will not, some will be considered citizens and others will not. In particular, I propose to think of reproductive self-determination as a right that is differentially distributed, and at the same time as what is at stake in the struggles for the legalization of abortion. The categories of rights and citizenship in the feminist struggles of our time have been the object of dispute. I want then to think about the limitations and potentialities of both in the search for the construction of a more just world that seeks to minimize precariousness, rather than reproduce and maximize it. What inequalities does a discourse of rights reproduce? What other forms of citizenship are disputed in the street and collective actions around the legalization of abortion? What other citizenship do people with a uterus deserve to build and exercise? These are some of the questions that guide the present reflections.